Benchmarking Product Service System of Generator Set Distributors - Tiurindah, Venny Violetta; Sofianti, Tanika Dewi (UI Scholars Hub, 2018)
Power generation is an industry that is essential to sustain daily life and competes with generator set distributors. The product service system of distributors must be improved to survive the competition. This research aims to develop tools for benchmarking the product service system of generator set distributors. Benchmarking identifies gaps between a product and other competitors’ products. In this work, a product service system board is used to visualize the current product service system of a generator set distributor. A PPIAF framework and a SERVQUAL framework are adapted to assess product performance and service quality, respectively. AHP is used as weighting method. The survey results provide ideas for improving the current product service system of generator set distributors. Further studies must use detailed measure weighting methods and implement the product service system board to assess service quality.